Pyroptosis, a new bridge to tumor immunity. Issue 10 (10th August 2021) - Li, Lisha; Jiang, Mingxia; Qi, Ling; Wu, Yiming; Song, Dongfeng; Gan, Junqing; Li, Yanjing; Bai, Yuxian
Abstract: Pyroptosis refers to the process of gasdermin (GSDM)‐mediated programmed cell death (PCD). Our understanding of pyroptosis has expanded beyond cells and is known to involve extracellular responses. Recently, there has been an increasing interest in pyroptosis due to its emerging role in activating the immune system. In the meantime, pyroptosis‐mediated therapies, which use the immune response to kill cancer cells, have also achieved notable success in a clinical setting. In this review, we discuss that the immune response induced by pyroptosis activation is a double‐edged sword that affects all stages of tumorigenesis. On the one hand, the activation of inflammasome‐mediated pyroptosis and the release of pyroptosis‐produced cytokines alter the immune microenvironment and promote the development of tumors by evading immune surveillance. On the other hand, pyroptosis‐produced cytokines can also collect immune cells and ignite the immune system to improve the efficiency of tumor immunotherapies. Pyroptosis is also related to some immune checkpoints, especially programmed death‐1 (PD‐1) or programmed death‐ ligand 1 (PD‐L1). In this review, we mainly focus on our current understanding of the interplay between the immune system and tumors that process through pyroptosis, and debate their use as potential therapeutic targets. Abstract : The immune response induced by pyroptosis activation is a double‐edged sword that affects all stages of tumorigenesis. On the one hand, the activation of inflammasome‐mediated pyroptosis and the release of pyroptosis‐produced cytokines alter the immune microenvironment and promote the development of tumors by evading immune surveillance. On the other hand, pyroptosis‐produced cytokines can also collect immune cells and ignite the immune system to improve the efficiency of tumor immunotherapies.